Biphasic Dose–Response Induced by PCB150 and PCB180 in HeLa Cells and Potential Molecular Mechanisms. Issue 1 (13th March 2020) - Zehra, Ainy; Hashmi, Muhammad Zaffar; Khan, Abdul Majid; Malik, Tariq; Abbas, Zaigham
The polychlorinated biphenyls (PCBs) are persistent and their dose-dependent toxicities studies are not well-established. In this study, cytotoxic and genotoxic effects of PCB150 and PCB180 in HeLa cells were studied. The 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assay indicated that the cell proliferation was stimulated at low doses (10 −3 and 10 −2 µg/mL for 12, 24, 48, and 72 hours) and inhibited at high doses (10 and 15 µg/mL for 24, 48, and 72 hours) for both PCBs. Increase in reactive oxygen species formation was observed in the HeLa cells in a time- and dose-dependent manner. Malondialdehyde and superoxide dismutase showed increased levels at high concentrations of PCBs over the time. Glutathione peroxidase expression was downregulated after PCBs exposure, suggested that both PCB congeners may attributable to cytotoxicity. Comet assay elicited a significant increase in genotoxicity at high concentrations of PCBs as compared to low concentrations indicating genotoxic effects. PCB150 and PCB180 showed decrease in the activity of extracellular signal–regulated kinase 1/2 and c-Jun N-terminal kinase at high concentrations after 12 and 48 hours. These findings may contribute to understanding the mechanism of PCBs-induced toxicity, thereby improving the risk assessment of toxic compounds in humans.